Review and Prospect of International Aquatic Training Research -- Based on Visualization Analysis of Big Data literature - Luo, Lin; Wang, Xiangfei; Song, Naiqing (2021 International Conference on Information Technology and Contemporary Sports (TCS), 2021)
By using the method of literature analysis, visualization software and mathematical statistics, the paper analyzes the periodical distribution, discipline characteristics,research hot spots evolution and frontier trend of international aquatic training research topics in the past 40 years, aiming to comprehensively understand the historical development and the forward trend of international aquatic training research from the macro perspective. The web of science core collection database was retrieved from 1980 to 2020. The results are presented as "Article", and the language is English, with"training in water" or "exercise in water" or " rehabilitation in water " or " recovery in water " or " water therapy " or " water exercise " or " aquatic training " or " water strength training " or " strength training in water " or " water aerobics training " or " aqua jogging " or " aquatic therapeutic exercise " or " hydrotherapy " or " aquatic exercise " or " aquatic fitness training" or "Tai Chi in the water" or "Halliwick therapy" or " Watsu training" or "Bad Ragaz training" or "water walking training " or " running in the water " or " water yoga " or " therapeutic swim " or " AI Chi therapy " or " water Zunba " or "water balance exercise" or "water Fitness" or "aquatic treadmill training" or " aquatic plyometric training" for the subject words, and then the data retrieval is carried out. Finally, 2133 effective research data are screened for visual analysis of Citespace5.5R5 softwar. The results show that the main subjects include sports science, rehabilitation, internal medicine, rheumatology, physiology, bone science ,gerontology and gerontology, neuroscience and neurology, public, environmental and occupational health and nursing science, which provide knowledge basis and academic support for international aquatic training research in the past 40 years. The research content of this field is rich and there are significant interdisciplinary researches. With the development of the depth and breadth of research in this field, the cooperation in scientific research has been increasing in interdisciplinary, regional and inter institutional fields. According to the characteristics of the heat evolution of international water motion research, the development history of water motion research in the past 40 years is divided into basic development stage, rapid development stage and high-speed development stage. The evolution of micro hot spots in different stages corresponds to the main line of sports research hot spot in water from macro perspective, and it always focuses on the aquatic training to assist health management, improve disease impact, improve functional quality, improve individual quality of life and increase sports performance. In recent five years, the international aquatic training research has been a hot spot,focusing on five disciplines: sports science, rehabilitation, gerontology and gerontology, bone science, public, environment and occupational health.